Population structure, sex ratio and growth of the seabob shrimp Xiphopenaeus kroyeri (Decapoda, Penaeidae) from coastal waters of southern Brazil - Grabowski, Raphael Cezar [UNESP] (2014)
This study evaluated the growth and population structure of Xiphopenaeus kroyeri in Babitonga Bay, southern Brazil. Monthly trawls were conducted from July 2010 through June 2011, using a shrimp boat outfitted with double-rig nets, at depths from 5 to 17 m. Differences from the expected 0.5 sex ratio were determined by applying a Binomial test. A von Bertalanffy growth model was used to estimate the individual growth, and longevity was calculated using its inverted formula. A total of 4,007 individuals were measured, including 1,106 juveniles (sexually immature) and 2,901 adults. Females predominated in the larger size classes. Males and females showed asymptotic lengths of 27.7 mm and 31.4 mm, growth constants of 0.0086 and 0.0070 per day, and longevities of 538 and 661 days, respectively. The predominance of females in larger size classes is the general rule in species of Penaeidae. The paradigm of latitudinal-effect does not appear to apply to seabob shrimp on the southern Brazilian coast, perhaps because of the small proportion of larger individuals, the occurrence of cryptic species, or the intense fishing pressure in this region. The longevity values are within the general range for species of Penaeidae. The higher estimates for longevity in populations at lower latitudes may have occurred because of the growth constants observed at these locations, resulting in overestimation of this parameter.